PERAN GURU DALAM PEMBENTUKAN KARAKTER KEWARGANEGARAANPESERTA DIDIK KELAS IV DI UPTD SD NEGERI DULOLONGKECAMATAN ALOR BARAT LAUT KABUPATEN ALOR - Mahmudin Aba Hasan; Sudarto Lukman Lema; Rusmin Mulyadin Tut (STKIP Muhammadiyah Kalabahi, 2026)
Abstract: This study aims to determine and describe two main things, namely (1) the role of teachers in the formation of civic character of fourth-grade students at the UPTD SD Negeri Dulolong, Alor Barat Laut District, Alor Regency, and (2) the driving and inhibiting factors that influence teachers in forming the civic character of students at the school. The researcher was also guided directly by two supervising lecturers, namely Mr. (Sudarto Lukman Lema) as supervisor I and Mr. (Rusmin Mulyadin Tut) as supervisor II. Based on the background of this study, it is based on the importance of civic character education at the elementary school level as an effort to form a generation with character, love for the homeland, responsibility, and ability to live in society according to national values. This study uses a qualitative method with a descriptive approach. Data collection was carried out through interview, observation, and documentation techniques. The research subjects consisted of fourth-grade teachers, students, and parents of students. Data were analyzed descriptively qualitatively through the stages of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the role of teachers in the formation of civic character in students at the UPTD SD Negeri Dulolong includes the role of facilitator, guide, motivator, and role model. Teachers not only teach civics material, but also foster students through exemplary attitudes, habits, and character building in the school environment. In addition, this study also found that the driving factors that influence the success of teachers in forming civic character in students include student enthusiasm, parental support, cooperation between school parties, the availability of infrastructure, a conducive school environment, and a curriculum that supports civic values. Meanwhile, inhibiting factors include the lack of involvement of some parents at home, low discipline of some students, and limited facilities to support character activities at school. Thus, the success of the formation of civic character in students at this school is influenced by the integration of various driving factors, the ability of teachers to carry out their roles optimally, and the school's strategy in overcoming various obstacles faced. Keywords: role of teachers, , citizenship character.